Psychiatric epidemiology in Turkey: Main advances in recent studies and future directions - (:unkn) unknown (Turkish Association of Nervous and Mental Health, 2014)
Objective: To overview and evaluate the main findings, methodological shortcomings, and time trends of the recent psychiatric epidemiology studies in Turkey, as well as to provide areas prone for development in forthcoming research. Method: PubMed and Turkish Psychiatry Index were screened to identify relevant studies. Any epidemiological study from 2000 to 2012 with a general population or unique sub-population sample was included. Papers and results were classified as depression, anxiety, psychotic, dissociative, conversion, personality, alcohol and substance abuse, and trauma-related disorders, and common geriatric disorders. Results: There are various epidemiological studies on various psychiatric disorders in Turkey. However, there are main shortcomings and trends in research that subsequently stagnate current psychiatric epidemiological research. First, epidemiological studies were mainly conducted for academic purposes, not for addressing epidemiological issues or issues of health policy. Second, studies mainly focused on particular fields and institutions, which led to non-systematic accumulation of epidemiological results. Third, although Turkey is a natural laboratory of social conflicts and disasters, there were few studies with a focus on probable outcomes. Fourth, high-quality epidemiological studies with disseminating results tended to decrease, even in common mental disorders such as depression. Fifth, there were very few epidemiological studies using contemporary designs such as followup, genetic, or biomarker data in the general-population. Conclusion: Although psychiatric epidemiological studies of the last decade provide a suitable ground for future challenges, current trends in this research area has tended to stagnate, despite the potential for unique contributions. Forthcoming studies and researchers may notice novel methodological developments in epidemiology, with a growing attention on rapid urbanization, natural disasters, social conflicts, and migration.
Keywords: Epidemiology; Psychiatry; Risk factors; Trends; Turkey